The influence of total quality of campus life on student satisfaction and student engagement - Nur Rifhan A. Rahim, 1988-, author; Ahmad Jusoh, supervisor; Hamdan Said, 1964-, supervisor; Sekolah Perniagaan Antarabangsa Azman Hashim (Johor Bahru, Johor : Universiti Teknologi Malaysia, 2019)
Thesis (Ph.D (Pengurusan)) - Universiti Teknologi Malaysia, 2019